PENERAPAN STRATEGI PEMBELAJARAN QUICK ON THE DRAW UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS XI SMAN 6 PEKANBARU - Silitonga, May Exaudi; Z, Fakhruddin; Syahril, Syahril (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This research aims to determine the cognitive learning outcomes of students through the application of quick on the draw learning strategies. This research design uses posttest only control group design. The population of this study were all students of class XI IPA SMAN 6 Pekanbaru in the 2023/2024 school year with a sample of 71 people from class XI IPA 3 and XI IPA 5. The data analysis techniques used in this study were descriptive analysis techniques and inferential analysis. This research instrument is a cognitive learning outcome test consisting of 20 multiple choice questions. The results of the research in the experimental class showed an average value of 74.03% and the control class amounted to 60.71%. Based on these results, it can be seen that the cognitive learning outcomes of students increased by 13.32%. The normality test on the research data has a value of Sig. 0.180 for the experimental class and 0.81 for the control class. While the homogeneity test obtained a Sig value. 0,464. So that the quick on the draw learning strategy can be applied to Physics learning to improve students' cognitive learning outcomes.